1991
DOI: 10.1136/pgmj.67.785.247
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum iron levels in cases of Japanese encephalitis

Abstract: Summary:Forty-one children with acute laboratory confirmed Japanese encephalitis were studied. Serum iron concentrations were consistently low following Japanese encephalitis virus infection, with the levels being of prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The histopathology of JE has been studied in great detail [5], while little is known regarding biochemical alteration during infection. Our earlier studies revealed a significant fall in serum iron levels in JEV infection, both in humans [6] and in mice [7], caused by the action of macrophage-derived factor, which blocks the release of iron from splenic reticuloendothelial cells [7]. We recently showed leakage of plasma protein and infectious JEV in urine [8].…”
Section: Introductionmentioning
confidence: 99%
“…The histopathology of JE has been studied in great detail [5], while little is known regarding biochemical alteration during infection. Our earlier studies revealed a significant fall in serum iron levels in JEV infection, both in humans [6] and in mice [7], caused by the action of macrophage-derived factor, which blocks the release of iron from splenic reticuloendothelial cells [7]. We recently showed leakage of plasma protein and infectious JEV in urine [8].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported a significant fall in serum iron levels both in mice with JEV infection (Bharadwaj et al . 1991a) and in humans (Bharadwaj et al . 1991b).…”
Section: Introductionmentioning
confidence: 99%